Stabilization of Nanocrystalline Silver by Sella and Mansoori Rice Starch - Singh M.K.; Singh M.; Verma J.L.; Kumar N.; Mandal R.K. (My University, 2025)
The silver nanoparticles (AgNPs) have been synthesized by utilizing starch got from rice to serve as stabilizer and reducing agent in presence of sodium hydroxide. Two varieties of rice viz. Mansoori and Sella grown in Uttar Pradesh (India) were utilized for getting starch in this investigation. The starch hydrolysis yields glucose for the reduction of silver nitrate precursor. UV–Vis spectra showed localized surface plasmon resonance (LSPR) absorption peaks at 400 nm and 412 nm indicating the formation of AgNPs in Mansoori and Sella rice-starch respectively. Comparison of absorption plots based on Mie scattering with those of experimental results showed that diameter of AgNPs in sol statesare ~11 and ~16 nm for the aforesaid rice-starches. Suspension of the AgNPs formed by Sellaand Mansoori rice-starches was found to be stable for more than 8 and 4 months respectively. The particle sizes assessed by Transmission Electron Microscopy (TEM) are ~11 and ~12 nm for AgNPs stabilized by Mansoori and Sella respectively. In contrast to these the sizes measured from atomic force microscopy (AFM) for the two are ~110 and ~73 nm respectively. They are bigger than those observed under TEM. Such a change in size can be understood by recalling that AFM is a surface investigative tool that sees particles inclusive of starch layer. © 2014, The Indian Institute of Metals - IIM.